Ultrasound Measured Depth of Pelvic Free Fluid Correlates Well with Blood Loss Volume in Patients with Ectopic Pregnancy - Shuai Tang; Qing Zhou; Yuelun Zhang; Lin Chen; Xuerong Yu; Yanming Zhang; Zhenhong Qi; Yu Xia; Yuguang Huang (Emergency Medicine International)
Purpose. The ultrasonic finding of pelvic free fluid which suggests the possibility of internal haemorrhage helps the determination of the severity of patients. Methods. We conducted a retrospective study investigating ultrasonic measurements and haemorrhage volumes in patients having an ectopic pregnancy in a single centre from January 2013 to November 2016. The logistic regression model was used to establish the prediction model for haemorrhage volumes. The diagnostic accuracy was evaluated by area under ROC curve (AUC) analysis. We employed 800 ml as the cut-off point of the haemorrhage and further set it to 1000 ml and 1200 ml in the sensitivity analysis. Results. The mean pelvic free fluid depths measured by TVS and TAS were 4.45 ± 2.15 cm and 4.45 ± 2.56 cm in the haemorrhage ≥800 ml group, while they were 2.48 ± 1.51 cm and 2.55 ± 1.19 cm in <800 ml group. AUCs and the corresponding cut-off points were 0.741 (95% CI 0.677 to 0.804) and 0.118 when predicted by the standardised depths of TVS and TAS, 0.784 (95% CI 0.696–0.872) and 2.95 cm by the raw depths of TVS, and 0.748 (95% CI 0.665–0.831) and 3.35 cm by the raw depths of TAS. Conclusions. The depth of pelvic free fluid measured by TVS and TAS can be used to predict blood loss volume in patients having an ectopic pregnancy. TVS may perform better than TAS.